Pemikiran Neo-modernisme dalam Hubungan Agama dan Negara di Indonesia: Studi Komparatif Pemikiran Nurcholish Madjid Dan Abdurrahman Wahid - Fitri, Donna Ramadhan; Afifi, Abdullah A; Abbas, Afifi Fauzi (IDRIS Darulfunun Institute, 2022)
Neo-modernism emerged when the term post-modernism began when the term began to become a common discourse when many experts began to get displeased with the negative effects that modernity, either from the aspect of sociocultural structure or scientific aspects. Neo-modernism, if traced to its existence, is in the thoughts of Fazlur Rahman (1970). While in Indonesia itself has Neo-modernism figures namely Nurcholish Madjid and Abdurrahman Wahid. As moralists and democrats, they have a complete, comprehensive, inclusive, and even free understanding of Islam. Therefore, their ideological and political actions often cause controversy. Even if they differ in practice, they have a paradigm of Islamic thought. Since Cak Nur put forward the jargon